Snail-overexpressing Cancer Cells Promote M2-Like Polarization of Tumor-Associated Macrophages by Delivering MiR-21-Abundant Exosomes - Hsieh, Chia-Hsin; Tai, Shyh-Kuan; Yang, Muh-Hwa (Neoplasia (New York, N.Y.), 2018)
Epithelial-mesenchymal transition (EMT) is a major event during cancer progression and metastasis; however, the definitive role of EMT in remodeling tumor microenvironments (TMEs) is unclear. Tumor-associated macrophages (TAMs) are a major type of host immune cells in TMEs, and they perform a wide range of functions to regulate tumor colonization and progression by regulating tumor invasiveness, local tumor immunity, and angiogenesis. TAMs are considered to have an M2-like, i.e., alternatively activated, phenotype; however, how these EMT-undergoing cancer cells promote M2 polarization of TAMs as a crucial tumor-host interplay during cancer progression is unclear. In this study, we investigated the mechanism of EMT-mediated TAM activation. Here, we demonstrate that the EMT transcriptional factor Snail directly activates the transcription of MIR21 to produce miR-21-abundant tumor-derived exosomes (TEXs). The miR-21-containing exosomes were engulfed by CD14+ human monocytes, suppressing the expression of M1 markers and increasing that of M2 markers. Knockdown of miR-21 in Snail-expressing human head and neck cancer cells attenuated the Snail-induced M2 polarization, angiogenesis, and tumor growth. In head and neck cancer samples, a high expression of miR-21 was correlated with a higher level of SNAI1 and the M2 marker MRC1. This study elucidates the mechanism of EMT-mediated M2 polarization through delivery of the miR-21-abundant exosomes, which may serve as a candidate biomarker of tumor progression and provide a potential target for intercepting EMT-mediated TME remodeling.